Wetland ecotourism in Sri Lanka: issues and challenges - Fernando, Sudusingha Liyanage Jothirathna; Noresah Mohd Shariff, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Ecotourism industry is growing and changing at a fast pace to be an increasingly important source of income and employment in many countries. According to the World Tourism Organization, ecotourism is recorded as the highest growing market in the tourism industry with an annual growth rate of 5 per cent worldwide and representing six per cent of the world’s GDP and 11.4 per cent of all consumers spending. Sri Lanka has tremendous ecotourism resources with great potential for further development in Southern Asia. At present tourism industry with ecotourism sector is a major foreign exchange generating industry in Sri Lanka. Since 2005, the sector of ecotourism has been developed under the policy decisions and legal coverage of tourism act No. 38 of 2005 which came into effect in October 2007. Despite the positive trends Sri Lanka’s ecotourism has negative environmental feedbacks in the forms of land degradation, land clearance, erosion, disturbances and loss of biodiversity, air and water pollution This paper examines these issues with the help of extensive and comprehensive literature reviews on ecotourism. Ecotourism trends delineated in this article are based on the ancillary statistical data from 1990 to date and issues and challenges are discussed within the three categories of culture, economy and environment.